Health and economic benefits of secondary education in the context of poverty: Evidence from Burkina Faso - Werner, Luisa K.; Ludwig, Jan Ole; Sié, Ali; Bagagnan, Cheik H.; Zabré, Pascal; Vandormael, Alain; Harling, Guy; De Neve, Jan-Walter; Fink, Guenther (PLOS ONE, 2022)
Even though formal education is considered a key determinant of individual well-being globally, enrollment in secondary schooling remains low in many low- and middle-income countries, suggesting that the perceived returns to such schooling may be low. We jointly estimate survival and monetary benefits of secondary schooling using detailed demographic and surveillance data from the Boucle du Mouhoun region, Burkina Faso, where national upper secondary schooling completion rates are among the lowest globally (<10%). We first explore surveillance data from the Nouna Health and Demographic Surveillance System from 1992 to 2016 to determine long-term differences in survival outcomes between secondary and higher and primary schooling using Cox proportional hazards models. To estimate average increases in asset holdings associated with secondary schooling, we use regionally representative data from the Burkina Faso Demographic Health Surveys (2003, 2010, 2014, 2017-18; N = 3,924). Survival was tracked for 14,892 individuals. Each year of schooling was associated with a mortality reduction of up to 16% (95% CI 0.75-0.94), implying an additional 1.9 years of life expectancy for men and 5.1 years for women for secondary schooling compared to individuals completing only primary school. Relative to individuals with primary education, individuals with secondary or higher education held 26% more assets (SE 0.02; CI 0.22-0.30). Economic returns for women were 3% points higher than male returns with 10% (SE 0.03; CI 0.04-0.16) vs. 7% (SE 0.02; CI 0.02-0.012) and in rural areas 20% points higher than in urban areas with 30% (SE 0.06; CI 0.19-0.41) vs. 4% (SE 0.01; CI 0.02-0.07). Our results suggest that secondary education is associated with substantial health and economic benefits in the study area and should therefore be considered by researchers, governments, and other major stakeholders to create for example school promotion programs.